2006
DOI: 10.1002/ace.206
|View full text |Cite
|
Sign up to set email alerts
|

Engaging spirituality in the transformative higher education classroom

Abstract: Rebecca e-mails her instructor the morning after class to say that she could not sleep after the evening's discussion about purpose in adult education. She describes a strongly felt need to incorporate a less individualistic focus in her academic program. Frank begins a morning meditation ritual after taking a course where the instructor includes a guided visualization during each class session. He says that it helps with his ability to concentrate and express his creativity. In her evaluation of a course that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 8 publications
0
47
0
1
Order By: Relevance
“…Lindholm and Astin (2008) investigated faculty spirituality and the use of student-centered approaches to undergraduate teaching. Tolliver and Tisdell (2006) Some studies have found gender-based distinctions concerning personal spirituality.…”
Section: Discussionmentioning
confidence: 99%
“…Lindholm and Astin (2008) investigated faculty spirituality and the use of student-centered approaches to undergraduate teaching. Tolliver and Tisdell (2006) Some studies have found gender-based distinctions concerning personal spirituality.…”
Section: Discussionmentioning
confidence: 99%
“…of public institution students and 22.2% of private institution students "frequently" "felt at peace" and, that 24% and 25.4% of public and private institution students, respectively, responded they had frequently been able to find meaning in times of hardship and one can begin to see the disconnect that studies in this area are seeking to expose (Astin, 2004;Bryant & Astin, 2008;Tisdell, 2003Tisdell, , 2008Tolliver & Tisdell, 2006).…”
Section: Current Studymentioning
confidence: 99%
“…Many (Barry & Nelson, 2005;Wink & Dillon, 2002;Astin, 2003Astin, , 2004Tolliver & Tisdell, 2006) would agree with Love and define religion as, "a shared system of beliefs, principles or doctrines related to a belief in and worship of a supernatural power or powers regarded as creator(s) and governor(s) of the universe" (Love, 2001, p. 8). Love (2001 states that while religion and spirituality significantly overlap in the ideal world, "there are religious people tied so closely to dogma and doctrine as to be disconnected from issues of the spirit, and people who disavow any notion of or connection with religion yet are deeply involved in a search for meaning, wholeness, and purpose" (p. 8).…”
Section: Faith Spirituality Religionmentioning
confidence: 99%
See 2 more Smart Citations